ARENDT’S THEORY OF JUDGMENT FOR A POSTAPARTHEID SOUTH AFRICA (The Pretoria Student Law Review, 2021)
In this essay I will attempt to examine the ways in which judgment as described by Arendt, could have be applied to the decision of the court in Three Rivers Ratepayers Association v Northern Metropolitan in order to reach a more just decision than the court a quo. The court a quo ordered the eviction of a group of homeless individuals from land owned by the applicants. The evicted group was destitute and the court order made no mention of assisting them in finding alternative accommodation. From this situation, I will infer that an application of Arendt’s theory of judgment may lead to a space where homelessness, poverty or class disempowerment can be addressed, ultimately resulting in a new sense of justice in postapartheid South Africa. I will apply Arendt’s theory alongside the theories of Boyd White exemplified in his reference to ‘tensions’, Dugard’s disillusion with the formalism within the South African judiciary and Klare’s notion of ‘transformative constitutionalism’. These four theorists will collectively demonstrate how the decision in the court in the Three Rivers case failed to employ a more careful process of judgment thus neglecting an important opportunity to encourage the development of judgment as an art where the creation of justice is a real possibility.
Keywords: eviction; homeless individuals; Arendt; transformative constitutionalism; Three Rivers Ratepayers Association v Northern Metropolitan; justice